2006
DOI: 10.1002/mrd.20546
|View full text |Cite
|
Sign up to set email alerts
|

High iNOS mRNA and protein levels during early third trimester suggest a role for NO in prelabor cervical ripening in the bovine

Abstract: Nitric oxide (NO) plays a key role in the processes leading to cervical softening prior to labor. Inducible nitric oxide synthase (iNOS) contributes most to the increased production of NO during labor, as demonstrated in the rat cervix, or at term pregnancy in women. Changes in expression of iNOS during late gestation have not yet been studied longitudinally in any species, because repeatedly taking biopsies could not be performed. iNOS mRNA (n = 6) and protein expression (n = 3) in serial cervical biopsies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…According to this principle, we could type the NOS easily. Here, we used the NOS examining kit (The first substation of Jiang Cheng bioengineering institute, Nanking) to detect the serum iNOS activity in differential samples, the experimental process was performed according to the instruction manual and previously reported [23]. Briefly, under the 530 nm wavelength, we first detected the absorbance of differential samples with the chromatometry method, then according the following formula to calculate the iNOS activity.…”
Section: Methodsmentioning
confidence: 99%
“…According to this principle, we could type the NOS easily. Here, we used the NOS examining kit (The first substation of Jiang Cheng bioengineering institute, Nanking) to detect the serum iNOS activity in differential samples, the experimental process was performed according to the instruction manual and previously reported [23]. Briefly, under the 530 nm wavelength, we first detected the absorbance of differential samples with the chromatometry method, then according the following formula to calculate the iNOS activity.…”
Section: Methodsmentioning
confidence: 99%
“…2002). An earlier study of the cervix of pregnant and parturient cows showed that the expression of GAPDH was highly correlated ( r = 0.9) with the expression of actin‐ β (Aalberts et al. 2007), therefore GAPDH was regarded as a household gene and used as reference.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was performed using a mathematical model for the relative expression ratio in real-time PCR, the 2 -DDCt -method (Livak and Schmittgen 2001;De Preter et al 2002). An earlier study of the cervix of pregnant and parturient cows showed that the expression of GAP-DH was highly correlated (r = 0.9) with the expres-sion of actin-b (Aalberts et al 2007), therefore GAPDH was regarded as a household gene and used as reference.…”
Section: Rt-pcr For Sma Connexin-43 Vimentin and Desminmentioning
confidence: 99%
See 2 more Smart Citations